Schooling experiences of learners from low socio-economic status background in Lesotho - Nyaphisi, M.; Mosia, P. A. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Efforts to provide inclusive education in Lesotho started in the late 1980s with the Policy Statement on Special Needs Education. They continued until 2018 when the Ministry enacted the Lesotho Inclusive Education Policy, which focused mainly on disability inclusion. Lesotho has a large population living below the poverty line, but low socio-economic status does not constitute part of the special education needs addressed by the education system. Underpinned by an interpretivist paradigm and the capability approach, this case study sought to explore how the schooling experiences of learners from low socio-economic status reflect the learners’ academic potential. Participants were purposively selected, and data was generated through semi-structured interviews and analysed through interpretative phenomenological analyses. The study found that learners from low SES experience various psychosocial barriers to learning, such as the lack of amenities to learn, inappropriate role models to ignite their interest in schooling and being victims of domestic violence. Some learners encounter barriers that directly affect their performance, motivation, and retention in school when not attended to. This paper recommends that a large-scale study, representative of the national demographics, be conducted to explore how low SES affects educational outcomes. The results must inform how the Lesotho education system can develop policies and regulations that guide how schools must identify and adequately support all learners to attain their maximum potential.
Journal article of African Perspectives of Research in Teaching and Learning Journal Issue 2, Volume 9, 2025
Keywords: Capabilities; Inclusiveness; Lesotho; Policies; Socio-economic status; Secondary schooling; High school students -- economic conditions; Inclusive education -- Lesotho; Socio-economic status